UPAYA BHUTAN DALAM MENINGKATKAN ENERGY SECURITY MELALUI KERJASAMA HYDROPOWER DENGAN INDIA - Dewi Suciantini, Ni Kade; Priadarsini, Ni Wayan Rainy; Suwecawangsa, Adi Putra (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL); Vol 1 No 1 (2021): Jurnal DIKSHI, 2021)
This study aims to analyze Bhutan's efforts to improve energy security through hydropower cooperation with India. Bhutan has great potential to become a successful country through the development of renewable energy and is starting to use secondary energy supplies as an electricity strategy whose economy is based on hydropower. This research discusses issues that address Bhutan's efforts to improve energy security through its cooperation with India. This research uses data collected through various sources including, literature studies such as research reports, theses, and journals and books. The results of this study see that Bhutan's ability to utilize hydropower resources is possible because of its very close relationship with its neighboring country, India. The relationship developed in the hydropower sector has become a favorable situation for both countries. Keywords: Bhutan, Hydropower, Cooperation, Energy Security, Strategy